Novel metabolic role for BDNF in pancreatic β-cell insulin secretion - Gianluca Fulgenzi (Nature Portfolio, 2020)
Glucose metabolism is regulated by hypothalamic brain functions and factors produced by peripheral tissues. Here, the authors show that the regulator of food intake Brain-derived neurotrophic factor is also produced and secreted by muscle and stimulates pancreas insulin release.